Evaluating the durability of two recycled aggregates to be used in basal drainage layer of landfills. - Rodrigues, G. (2013)
LNEC, in partnership with FCT-UNL, have studied the durability of steel slag and construction and demolition waste in the presence of a leachate collected at a municipal solid waste landfill, with the main purpose to evaluate the technical feasibility of their recycling in the leachate collection and removal layer of landfills. The waste durability was studied using the slake-durability test (SDT) proposed by ISRM. In order to test the behaviour of them in chemical and mechanical conditions more adverse than those specified in the mentioned ISRM method, the leachate collected was acidified with hydrochloric acid to decrease the initial pH from 7.6 to 5.5, and more 600 rotation cycles than those foreseen in the ISRM method were applied, respectively. A similar procedure was used to test the materials after their immersion for 15 days in the same acidified leachate. As a complement to SDT tests, a macro- and micropetrographic characterization of two waste as well as a characterization of their physical properties, either before or after SDT tests, were performed. The paper presents the main results obtained, compares the performance of two waste with the one of two natural geomaterials (basalt and limestone), and concludes with the assessment of the technical feasibility of their recycling in the mentioned application.